Examining endothelial function and carotid artery disease in patients with inflammatory bowel disease: a systematic review protocol - Hao Wu; Zhenguo Liu; Tingzi Hu; Meihua Xu; Hong Hao; Michael A Hill; Canxia Xu (BMJ Open)
Introduction Patients with inflammatory bowel disease (IBD) might be at an increased risk for the development of cardiovascular disease (CVD). The present protocol is developed to review and analyse published data to determine if patients with IBD have an increased CVD burden.Methods and analysis We will conduct a systematic review of all observational studies that examine endothelial function, arterial stiffness and carotid intima-media thickness in patients with IBD. Study selection will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, and study quality will be assessed using the Newcastle-Ottawa Scale. If sufficient data are available, a meta-analysis will be conducted. The overall effect sizes will be estimated using both fixed effects models and random effects models. Statistical heterogeneity will be calculated using Higgin’s (I2) tests. Subgroup analyses, conditional number of studies retrieved and their sample size, will be stratified according to participant disease category or gender or disease activity.Ethics and dissemination Formal ethics approval is not required as individual data will not be collected. The results will be disseminated through peer-reviewed publications, conference presentations and scientific news releases.PROSPERO registration number CRD42021274093.